Ideologi dan Politik Penerjemahan Al-Qur’an: Analisis Wacana Kritis terhadap Al-Qur’an dan Terjemahnya Bahasa Madura - Ahmad Zaidanil Kamil (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This article examines the ideological construction underlying the Madurese Qur’anic Translation produced by IAIN Madura as part of a state-initiated translation project. Using a qualitative approach based on Norman Fairclough’s Critical Discourse Analysis and in-depth interviews, this study analyzes the translation of Qur’anic verses related to Islam and politics, particularly sensitive terms such as awliyā’, khalīfah, and al-silm kāffah. The results show that at the textual level, this translation employs linguistic strategies through the selection of diction, transliteration, and differentiation of meaning, thereby framing sensitive terms within a moderate and inclusive religious perspective. At the level of discursive practice, this translation represents an institutional project that integrates linguistic, religious, and ideological interests in shaping the religious orientation towards the subject of religion. The reception of this text has been articulated in various ways, ranging from affirmative public acceptance and academic engagement through scientific studies to critical assessments from religious leaders. In the post-reform socio-cultural context of Madura, characterized by the strengthening of Islamist narratives and the contestation between conservative and moderate tendencies, this translation serves as an alternative discourse that aligns with the state’s project of Islamic moderation. These findings confirm that the translation of the Qur’an in Madura is not merely a linguistic practice, but rather an ideological arena where power relations and religious interests are negotiated.